Characteristics of peroxyacetyl nitrate (PAN) in the high-elevation background atmosphere of South-Central China: Implications for regional photochemical pollution. (1st June 2021) - Daocheng Gong,; Liao, Minping; Wu, Gengchen; Wang, Hao; Li, Qinqin; Chen, Yaqiu; Deng, Shuo; Zheng, Yu; Ou, Jie; Wang, Boguang
Abstract: Over the past decade, secondary pollution characterized by active photochemistry has sharply increased and become the major contributor to air pollution in China, despite the great reduction of primary emissions. Peroxyacetyl nitrate (PAN) is an excellent indicator of photochemical pollution. Observation of PAN in high-elevation atmosphere offers a rare opportunity to understand the degree of photochemical activity in a wide region. In this study, we conducted a field campaign at a high-altitude (1690 m a.s.l.) national background site on the border of South and Central China during photochemically polluted seasons (Sep–Nov 2018). PAN showed significantly higher concentrations than other high-elevation sites worldwide, with hourly mean and maximum values of 0.52 ± 0.45 ppbv and 2.33 ppbv, respectively. Episodes with much higher PAN levels (1.03 ± 0.40 ppbv) than backgrounds (0.24 ± 0.13 ppbv) were captured. Nighttime peaks suggested mixed impacts of regional transport and VOCs oxidation by nitrate radical and O3 . High background O3 (44.30 ± 0.44 ppbv) was derived from the significant positive correlation of O3 with PAN. Contributions of downward transported PAN from upper troposphere were found to be non-negligible. Further analyses revealed that regional transport from Central China contributed substantially to the high levels of PAN, with only a minor contribution coming from the south where the Pearl River Delta (PRD) metropolitan region is located. Our results might indicate the great achievement in air quality improvement in the PRD, and also suggest that a strategic shift of control focus from metropolitan to developing areas is urgently needed for mitigating the severe photochemical pollution in China. Graphical abstract: Image 1 Highlights: First observations of PAN in the high-elevation background atmosphere of South-Central China. Higher PAN concentrations than those at other high-elevation sites worldwide were observed. Relatively high background O3 was obtained from linear regression of O3 and PAN. Air masses coming from Central China significantly enhance the PAN levels. Strategic shift of control focus from metropolitan to developing areas in China is suggested.